KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH INITIAL PUBLIC OFFERING (IPO) - Fauzan, Muhammad; Risna Wijayanti (Jurnal Management Risiko dan Keuangan, 2022)
This research aims to analyze company’s financial performance before and after Initial Public Offering (IPO) and to show whether there are any significant differences of company’s financial performance before and after IPO. This research focuses onthe financial performance of PT. MNC Sky Vision, Tbk. The data was obtained from their annual financial reports from 2009 to 2019. And was analyzed using descriptive statistic and paired sample t-test in SPSS. The results show that Liquidity, Activity, Profitability, and Market Value ratios were decreasing before IPO and that Solvability have the opposite result.  Furthermore, Profitability and Market Value ratios were decreasing after IPO, while Liquidity and Solvability were volatile, Activity is the only ratio that was increasing after IPO. The results of the paired sample t-test show that Liquidity, Solvability, Activity, and Profitability ratios have no significant difference between before and after IPO.